Mrs Helena Aylward: A British Catholic mother, spouse and businesswoman in the Commercial Age (1705–1714). Issue 4 (6th September 2017) - Pizzoni, Giada
Abstract : Mrs Helena Aylward, as a Catholic merchant and investor, enriches the literature on both female Catholicism and on the Atlantic-Mediterranean trade. Recent historiography has stressed the importance of women in business, but Catholic women have been overlooked in the mercantile world and in the British fiscal-military economy. I contend that female Catholics were accustomed to their husband's dealings, and after bereavement, took financial responsibility for the family's business. Helena was proactive and did not limit herself to the exchanges already established by her husband. She moved independently and diversified her trade with financial investments. Mrs Aylward's involvement in business challenges the prevailing image of Catholic women as wives, patrons or nuns. She suggests a new economic role for British female Catholics: entrepreneurs that succeeded in a Protestant and patriarchal maritime world. 1